Acute mesenteric ischemia–like syndrome associated with suspected Spirocerca lupi aberrant migration in dogs. Issue 6 (18th October 2019) - Lerman, Omer; Israeli, Inbar; Weingram, Tomer; Benzioni‐Bar, Hadas; Milgram, Josh; Shipov, Anna
Abstract: Objective: To describe acute mesenteric infarction due to suspected Spirocerca lupi aberrant migration in 5 dogs. Case Series Summary: All dogs were large breed, none of which exhibited typical clinical signs associated with spirocercosis. All dogs were eventually diagnosed with septic peritonitis. On exploratory laparotomy, thickening of the jejunal arteries, surrounding mesojejunum, and segmental necrosis were identified. Similar thickening and hematoma formation were found in other regions of the mesentery. In 4 of the cases, the necrotic segment was located in the distal jejunum. Histology revealed thrombotic mesenteric vessels with intralesional S. lupi nematode larvae. Resection and anastomosis of the necrosed section was performed and all but 1 dog survived and were discharged within 1–6 days. New or Unique Information Provided: Spirocerca lupi is a potential cause of mesenteric infarction in endemic areas when no other obvious etiology is identified.